(3GdaVGA GdYehej h ehGbY THcGJ GdJhGUd GdZLJeGYj GdJTXj h EYGOI bQGAI Gdeaghe (B/s - (3eLehYI ef GdeDdajfs ((3LGeYI GdLRGFQ(B3;(3LGeYI hgQGf (B1 (3GMeO Hf HdI (B:s (3eNHQ GSJNOGeGJ h Jdbj GdefJLGJ GdEYdGejI h GdKbGaI aj GdLRGFQ ,s)
(3HejdGO GdCfJQfJ h JRGjO OhQgG GdEJUGdj h GfOaGY ehGbY GdJhGUd GdELJeGYj aj Oc GdMOhO GdaGUdI Hjf eGgh YGe h NGU h JZjjQ GdeeGQSI GdSjGSjI h JhSjY fWGbgG GcJSH eaghe GdaVGA GdYehej CgejI eMhQjI aj Ydhe GdZYdGe h GdZJUGd h YGO GdfbGT ef LOjO h HTcd CcKQ MOI Mhd GdYdGbI Hjf GdaVGA GdYehej h GdaVGA GdSjGSj h GdaVGA GdZYdGej h JHGjfJ GdehGba Hjf ef jQi Gf gPg GdehGbY SJchf eYhdG ddbVGA Ydi GdaVGA GdYehej HJTJjJg h SdH MjhjJg ef LhgQg GdfbGT h GdZSJNOGe GdYdfjddMLI h ef jQi Gf gPg GdehGbY JTcd aQUI JGQjNjI ddbVGA Ydi GdfRYI GdEbUGFjI GdJj GJSe HgG GdaVGA GdYehej GdHQLhGRj aj GdZQH h ENQGLg ef GdCReI GdJj bGOg EdjgG JdcS GdCMRGH GdSjGSjI h GfMQGaGJ hSGFd GdEJUGd GdLeGgjQj Yf OhQgG GdJfhjQjs
Keywords: (3GdejOjGs; (3GdaVGA GdYehejs